Political economy of crisis and reform in Ecuador, 2000-2005 - Carrell, R (2007)
Ecuador is tiny, heavily indebted, strategically insignificant, and was desperate for finance following a deep crisis in 1998-2000. The IMF is widely seen as 'all-powerful', and keen to exploit weaknesses to extract policy concessions. Given this, why was the IMF unable to achieve success on virtually any of the structural reforms it attempted to impose in Ecuador between 2000 and 2005? This thesis aims to explain this reform stasis following crisis in Ecuador. The investigation centres around a 'veto player analysis', a useful tool which has been underused in the political economy of reform literature. The thesis develops the concept and shows how it can be applied empirically, showing where veto power came from and how players constructed their own power. Seven cases of failed reforms are investigated: tax reform, civil service reform, LPG subsidy removal, customs reform, telecommunications and electricity privatisations, and reforms in the oil sector. These are compared to cases of relative 'success'. The analysis finds that policy stasis was due to a proliferation of societal and legislative 'veto players', who drew on the chronic instability of the Ecuadorian political system and took advantage of executive incapacity to issue credible threats to individuals and even entire administrations. Instability is found to facilitate each of these factors impeding reform. These findings throw doubt on an idea conventional in the literature, that economic crisis catalyses economic reform. The thesis argues that paradoxically, instability is at the root of policy stasis in Ecuador, and that in exacerbating instability, crisis impedes reform rather than catalysing it.